2021
DOI: 10.1097/fjc.0000000000001014
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis: The Effects of Prophylactic Proton Pump Inhibitor Treatment in Patients With Coronary Heart Disease Receiving Dual Antiplatelet Therapy

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 71 publications
0
9
1
Order By: Relevance
“…The results showed that PPI coadministration decreased the risk of GI complications but could increase the rates of MACEs, stroke, revascularization and ST, in line with previous studies ( Melloni et al, 2015 ; Hu et al, 2018 ). There were also no significant differences in the risks of all-cause mortality and cardiac death ( Hu et al, 2018 ; Li et al, 2021 ; Melloni et al, 2015 ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The results showed that PPI coadministration decreased the risk of GI complications but could increase the rates of MACEs, stroke, revascularization and ST, in line with previous studies ( Melloni et al, 2015 ; Hu et al, 2018 ). There were also no significant differences in the risks of all-cause mortality and cardiac death ( Hu et al, 2018 ; Li et al, 2021 ; Melloni et al, 2015 ).…”
Section: Discussionmentioning
confidence: 90%
“…However, the existing clinical studies of the association between cardiovascular events and the concomitant use of PPIs with aspirin-clopidogrel DAPT in CHD have been conflicting ( Ben Ghezala et al, 2022 ). Some meta-analyses were conducted to assess the clinical significance of this interaction and found that coadministration of PPIs could increase the rates of major adverse cardiovascular events (MACEs), stroke, revascularization, and stent thrombosis (ST) but not myocardial infarction (MI), all-cause mortality, or cardiac death ( Guo et al, 2021 ; Hu et al, 2018 ; Li et al, 2021 ; Melloni et al, 2015 ; Sherwood et al, 2015 ). Interestingly, two recent clinical studies reported that the rates of MI, all-cause mortality and cardiac death were significantly increased in PPI users compared to non-users ( Maret-Ouda et al, 2021 ; Mohammed et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with non-PPIs arm, the PPIs arm reduced the risk of GI complications. 16 Similar views were reported in both meta-analyses. However, there are some differences in our meta-analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Previous meta-analyses evaluated the strategy of PPIs combined with aspirin and P2Y 12 receptor inhibitors, but the results were inconsistent. 6,[15][16][17] Meanwhile, with the update of guidelines, more antithrombotic strategies have been proposed. We performed this meta-analysis and hypothesized that PPIs plus antithrombotic strategy can reduce the risk of GI bleeding without increasing ischemic events in patients with CAD.…”
Section: Introductionmentioning
confidence: 99%
“…This may be particularly relevant to the acute setting. Observational studies have suggested some interaction effects between proton pump inhibitors and DAPT, with a high degree of heterogeneity [94]. While the only large-scale RCT on the prophylactic use of proton pump inhibitors in patients receiving clopidogrel demonstrated reduced upper gastrointestinal bleeding without increasing ischemic risks [95,96], guidelines vary in terms of patient selection for such prophylactic use [97].…”
Section: Common P2y 12 I Drug Interactionsmentioning
confidence: 99%